A cross-border analysis on the harmonization of sustainability reporting among listed industrial companies from the ASEAN 5 - Floresca, Justine Gem R. (Animo Repository, 2016)
This study provides an analysis of the current harmonization level of sustainability reporting among the selected member countries in the ASEAN region. The countries selected were Indonesia, Malaysia, Philippines, Singapore and Thailand, the original five members of the ASEAN. The study aims to determine the current standing of sustainability reporting in the movement towards harmonization using the Global Reporting Initiative G4 (GRI G4) Sustainability Reporting Guidelines. It also seeks to determine if each company characteristics of age, size, and type of ownership have an impact on the preparation of sustainability reports. The harmonization index and the Wilcoxon Matched Pairs Signed Rank Test were used to determine the level of harmonization towards GRI G4 Guidelines while binary logistic regression was performed to test the impact of company characteristics of age, size, and type of ownership on the preparation of sustainability reports. Based on the results, there is no harmonization among the publicly listed industrial companies in the ASEAN 5. On the other hand, the company characteristics of size and type of ownership have a significant impact on the preparation of sustainability reports while age was found to have no significant impact.